The Coexistence of Kaum Mudo and Kaum Tuo: The Transformation of Islamic Education in Minangkabau - Abdullah A Afifi; Ferdi Yufriadi (Tarikhuna: Journal of History and History Education, 2024)
The coexistence of kaum mudo (Muhammadiyah and Sumatera Thawalib) and kaum tuo (Perti) in the context of Islamic education in Minangkabau reflects a significant transformation within the traditional framework of this educational system. This study aims to explore this transformation and its implications. Utilizing ethnographic methods, including participant observation and interviews, the research delves into the dynamics of Islamic education in Minangkabau society. Findings reveal a complex interplay between traditional practices and modern influences, as younger generations navigate their identity within an evolving educational landscape. While older generations uphold traditional teaching methods and values, younger individuals engage with contemporary educational approaches and technologies. Despite these apparent differences, there exists a symbiotic relationship between kaum mudo and kaum tuo, wherein traditional wisdom is passed down alongside modern knowledge. This coexistence fosters a unique learning environment that blends heritage with innovation, preserving the essence of Islamic education while embracing contemporary advancements. The study concludes that this coexistence serves as a testament to the resilience and adaptability of Islamic education in Minangkabau, ensuring its relevance and continuity in the face of societal changes.